2015
DOI: 10.1016/j.pmrj.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Hand–Exercise Session on Manual Dexterity and Strength in Persons with Parkinson Disease: A Randomized Controlled Trial

Abstract: A single hand-exercise session showed an improvement in manual dexterity and strength in persons with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 51 publications
(57 reference statements)
0
42
0
1
Order By: Relevance
“…The longest intervention is reported in the study of Corcos et al, in which they assessed the effects of 2 years of progressive resistance training 28. As regards the length of the training session, the shortest was the single 15-minute hand exercise reported by Mateos-Toset et al30 and the longest was the double 30-minute session of specific training plus one additional 60-minute session of common exercises, reported by Arcolin et al26 Most of the reviewed articles assessed the post-treatment effects, and only three reported the long-term effects 31,32,35,36…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The longest intervention is reported in the study of Corcos et al, in which they assessed the effects of 2 years of progressive resistance training 28. As regards the length of the training session, the shortest was the single 15-minute hand exercise reported by Mateos-Toset et al30 and the longest was the double 30-minute session of specific training plus one additional 60-minute session of common exercises, reported by Arcolin et al26 Most of the reviewed articles assessed the post-treatment effects, and only three reported the long-term effects 31,32,35,36…”
Section: Resultsmentioning
confidence: 99%
“…The range of disease severity assessed by the Hoehn and Yahr scale is 1.5–3; the lowest mean age considered is 58.6±5.6 years old28 and the maximum is 75.7±7.2 years old,32 and the number of subjects per study ranged from 22 to 60. The lowest intervention per week considered is reported in the study of Mateos-Toset et al, in which they highlighted the effects of a brief exercise session of hand training with therapeutic putty 30. The longest intervention is reported in the study of Corcos et al, in which they assessed the effects of 2 years of progressive resistance training 28.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is very little evidence for exercise to improve hand function. A recent controlled pilot study found positive effects on dexterity and strength immediately following a single hand exercise session with therapeutic putty [89].…”
Section: Exercisementioning
confidence: 99%